A Meta-Analysis of Single-Case Research on Behavior Contracts: Effects on Behavioral and Academic Outcomes Among Children and Youth. (March 2015) - Bowman-Perrott, Lisa; Burke, Mack D.; de Marin, Sharon; Zhang, Nan; Davis, Heather
The purpose of this meta-analysis was to quantitatively summarize the single-case research (SCR) literature on the use of behavior contracts with children and youth. This study examined the efficacy of behavior contracts on problem behaviors and academic behaviors across 18 SCR studies. Academic and behavioral outcomes were examined for 58 children and youth ages 5 to 21 using the TauU effect size index. Results indicated the overall moderate effect of the use of behavior contracts was ES = .57 (95% confidence interval [CI95 ] = [0.55, 0.58]) with a range of effects across studies (ES = .27 to ES = 1.00). Moderator analyses indicated that behavior contracts are beneficial for students regardless of grade level, gender, or disability status. Findings suggest that the intervention is more effective in reducing inappropriate behaviors than increasing appropriate behaviors, and that academic outcomes are positively affected by behavior contracting.